Endometriosis among African women. Issue 3 (26th September 2022) - Mecha, Ezekiel O; Njagi, Joseph N; Makunja, Roselydiah N; Omwandho, Charles O A; Saunders, Philippa T K; Horne, Andrew W
Abstract : Endometriosis has long been wrongly perceived to be rare among women of African descent. The misconception about the prevalence of endometriosis among African women has significantly contributed to long diagnostic delays, limited access to diagnosis and care, and a scarcity of research on the condition among African women. In this commentary, we highlight the prevalence of endometriosis among African women, the state of endometriosis care in Africa, and the gaps in knowledge that need to be addressed. Based on the available data, the prevalence of endometriosis in Africa is likely higher than previously thought, with varying subtypes. There is a long diagnostic delay of endometriosis among African women. Additionally, endometriosis care in Africa from the general population and health practitioners is poor; this can be attributed to the high diagnostic cost, scarcity of trained specialists, as well as patients' inability to express their symptoms due to societal taboos surrounding menstrual health. Public sensitization on endometriosis may help improve endometriosis diagnosis and care in Africa. Lay summary: Endometriosis is a condition in which tissue like the uterine lining is found outside the uterus, causing women to experience pain especially before, during, or after menstruation. Although endometriosis affects an estimated 176 million women worldwide, it has been wrongly reported that endometriosis is a rare condition among African women, mainly due to lack of awareness among healthcare providers and historical bias. In the current commentary, we discuss the prevalence of endometriosis, the diagnostic delays, and the care of endometriosis among black African women living in the African continent. Much of the literature has demonstrated (falsely) that endometriosis is rare in Black women compared to White ethnicity. African women experience a long diagnostic delay and do not receive appropriate care. Public awareness of endometriosis may help improve diagnosis delay and endometriosis care in Africa.